Meniscal and Articular Cartilage Predictors of Clinical Outcome After Revision Anterior Cruciate Ligament Reconstruction. (July 2016) - ,
Background: Revision anterior cruciate ligament (ACL) reconstruction has been documented to have worse outcomes compared with primary ACL reconstructions. Purpose/Hypothesis: The purpose of this study was to determine if the prevalence, location, and/or degree of meniscal and chondral damage noted at the time of revision ACL reconstruction predicts activity level, sports function, and osteoarthritis symptoms at 2-year follow-up. The hypothesis was that meniscal loss and high-grade chondral damage noted at the time of revision ACL reconstruction will result in lower activity levels, decreased sports participation, more pain, more stiffness, and more functional limitation at 2 years after revision surgery. Study Design: Cohort study; Level of evidence, 2. Methods: Between 2006 and 2011, a total of 1205 patients who underwent revision ACL reconstruction by 83 surgeons at 52 hospitals were accumulated for study of the relationship of meniscal and articular cartilage damage to outcome. Baseline demographic and intraoperative data, including the International Knee Documentation Committee (IKDC) subjective knee evaluation, Knee injury and Osteoarthritis Outcome Score (KOOS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and Marx activity score, were collected initially and at 2-year follow-up to test the hypothesis. Regression analysis was used to control for age, sex, body mass index, smoking status, activity level, baseline outcome scores, revision number, time since last ACL reconstruction, incidence of having a previous ACL reconstruction on the contralateral knee, previous and current meniscal and articular cartilage injury, graft choice, and surgeon years of experience to assess the meniscal and articular cartilage risk factors for clinical outcomes 2 years after revision ACL reconstruction. Results: At 2-year follow-up, 82% (989/1205) of the patients returned their questionnaires. It was found that previous meniscal injury and current articular cartilage damage were associated with the poorest outcomes, with prior lateral meniscectomy and current grade 3 to 4 trochlear articular cartilage changes having the worst outcome scores. Activity levels at 2 years were not affected by meniscal or articular cartilage pathologic changes. Conclusion: Prior lateral meniscectomy and current grade 3 to 4 changes of the trochlea were associated with worse outcomes in terms of decreased sports participation, more pain, more stiffness, and more functional limitation at 2 years after revision surgery, but they had no effect on activity levels. Registration: NCT00625885